2014
DOI: 10.1007/s40091-014-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Static stability of a viscoelastically supported asymmetric sandwich beam with thermal gradient

Abstract: The static stability of an asymmetric sandwich beam with viscoelastic core on viscoelastic supports at the ends and subjected to an axial pulsating load and a steady, one-dimensional temperature gradient is investigated by computational method. The equations of motion and associated boundary conditions are obtained using the Hamilton's energy principle. Then, these equations of motion and the associated boundary conditions are nondimensionalised. A set of Hill's equations is obtained from the non-dimensional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…These parameters show similar behaviour as per the past literatures. 14, 15 The plots are not provided to limit the number of figures.…”
Section: Results Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters show similar behaviour as per the past literatures. 14, 15 The plots are not provided to limit the number of figures.…”
Section: Results Assessmentmentioning
confidence: 99%
“…The successive integration of equilibrium differential equations and the associated boundary conditions were studied by Nassar and Horton 13 to achieve the deflection of a beam with rotational restraint. Nayak et al 14 analysed the buckling strength of a sandwich beam with viscoelastic end support and observed that the end flexibilities improved the stability. Pradhan and Dash 15 considered viscoelastic end support with a tapered sandwich beam and analysed the impact of the end flexibilities on the beam’s dynamic stability.…”
Section: Introductionmentioning
confidence: 99%
“…They considered the coupling of axial and transverse vibration and of elastic deformations and rigid motion. Nayak et al 15 investigated the stability of a sandwich beam on viscoelastic supports subjected to a pulsating axial load with temperature gradient. Soltani et al 16 proposed a numerical solution based on power series method to derive the critical buckling loads and frequency of free vibrations for tapered thin beams.…”
Section: Introductionmentioning
confidence: 99%